Histone deacetylase 1 and 2 are essential for murine neural crest proliferation, pharyngeal arch development, and craniofacial morphogenesis. Issue 12 (5th September 2017) - Milstone, Zachary J.; Lawson, Grace; Trivedi, Chinmay M.
Abstract : Background : Craniofacial anomalies involve defective pharyngeal arch development and neural crest function. Copy number variation at 1p35, containing histone deacetylase 1 (Hdac1), or 6q21‐22, containing Hdac2, are implicated in patients with craniofacial defects, suggesting an important role in guiding neural crest development. However, the roles of Hdac1 and Hdac2 within neural crest cells remain unknown.Results: The neural crest and its derivatives express both Hdac1 and Hdac2 during early murine development. Ablation of Hdac1 and Hdac2 within murine neural crest progenitor cells cause severe hemorrhage, atrophic pharyngeal arches, defective head morphogenesis, and complete embryonic lethality. Embryos lacking Hdac1 and Hdac2 in the neural crest exhibit decreased proliferation and increased apoptosis in both the neural tube and the first pharyngeal arch. Mechanistically, loss of Hdac1 and Hdac2 upregulates cyclin‐dependent kinase inhibitors Cdkn1a, Cdkn1b, Cdkn1c, Cdkn2b, Cdkn2c, and Tp53 within the first pharyngeal arch.Conclusions: Our results show that Hdac1 and Hdac2 function redundantly within the neural crest to regulate proliferation and the development of the pharyngeal arches by means of repression of cyclin‐dependent kinase inhibitors. Developmental Dynamics 246:1015–1026, 2017 . © 2017 Wiley Periodicals, Inc. Key Findings: Ablation of Hdac1 and Hdac2 within murine neural crest progenitor cells causes severe hemorrhage and embryonic lethality. Hdac1 and Hdac2 regulate first pharyngeal arch and craniofacial development. Hdac1 and Hdac2 repress cyclin‐dependent kinase inhibitors within the first pharyngeal arch.